COMPARATIVE LEGAL STUDIES: ROMANO-GERMANIC LEGAL SYSTEMS IN THE ASIA-PACIFIC STATES - Dmitry A. Verkhoturov; Andrey A. Verkhoturov (Сравнительная политика)
The article analyzes the differences in the national legal doctrines of the Asia-Pacific countries included in the Romano-Germanic legal family of legal systems. The article shows that various Pacific Rim countries of the same legal family have substantial differences between national legal systems. The article also identifies main trends of comparative legal studies development in these countries.